중증환자 긴급치료병상의 건축계획 평가를 위한 기준 도출 - 박서원; 권순정 (의료·복지 건축, 2024)
Purpose: This study aims to establish evaluation criteria for rapidly converted negative pressure isolation unit(RCNIU) by converting general wards into infectious disease isolation wards, addressing the lack of standards for evaluating existing facilities. The goal is to provide reference data for facility planning and improve the performance of rapidly converted negative pressure isolation units. Methods: Installation standards and existing evaluation criteria for infectious disease isolation wards in Korea were analyzed to create a framework for RCNIU evaluation. An evaluation table was developed, categorizing items into importance levels. Expert surveys in hospital architecture and medical welfare provided average values for scoring each item. Results: Evaluation criteria were organized into ‘required provision of space, installation conditions, proper location, and circulation plan.’ Key items included ’installation of inpatient rooms and attached toilets in the negative pressure area‘ and ‘securing a single bed room area of 11.6㎡ or more’. The "separation of clean and contaminated circulation was also highlighted as critical. Overall, room size, negative pressure conditions, and circulation planning were the most significant factors. Implications: Systematic evaluation criteria can enhance the functionality of RCNIU. Further research should analyze hospital layouts and apply the framework to assess existing facilities, guiding future improvements.
Keywords: 중증환자 긴급치료병상; 건축계획; 평가기준; 팬데믹; Rapidly Converted Negative Pressure Isolation Unit(RCNIU); Architectural Planning; Evaluation Criteria; Pandemic